The Effect of Trust, Goods Prices and Pocket Money on the Level of E-Commerce Transactions in UNNES Class 2017 Students - Agung Steven (Ikatan Sarjana Ekonomi Indonesia Cabang Semarang, 2020)
The purpose of this study was to determine the effect of trust, the price, and income on the level of e-commerce transactions in 2017 UNNES students. This research is a direct survey research. The study uses Linear Regression Analysis to determine the magnitude of the influence between X variables on Y. The results of this study indicate that of the 99 students who became respondents in this study as many as 31 students (31.31%) had e-commerce transaction rates that were included in the very high category, 57 students (48.48%) had e-commerce transaction rates that were included in the high category, 11 students (33.33%) had e-commerce transaction rates included in the moderate category.